2019
DOI: 10.3390/rs11111275
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Mapping of Forest Structure Parameters from Open Access Satellite Images: Development of a Generic Method with a Study Case on Coniferous Plantation

Abstract: Temperate forests are under climatic and economic pressures. Public bodies, NGOs and the wood industry are looking for accurate, current and affordable data driven solutions to intensify wood production while maintaining or improving long term sustainability of the production, biodiversity, and carbon sequestration. Free tools and open access data have already been exploited to produce accurate quantitative forest parameters maps suitable for policy and operational purposes. These efforts have relied on differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 66 publications
(77 reference statements)
1
35
0
2
Order By: Relevance
“…The results indicated that texture features of SAR data were much more helpful than original backscatters to forest volume prediction, which was consistent with existing researches [52,78]. However, textural indices from Sentinel-1 was marginal in this study for volume mapping compared to the previous finding [79]. It was resulted from the decrease in the heterogeneity by texture analysis and large variations of stand volume in the study area.…”
Section: Multi-sensor Satellite Predictors Of Forest Volume Mappingsupporting
confidence: 87%
“…The results indicated that texture features of SAR data were much more helpful than original backscatters to forest volume prediction, which was consistent with existing researches [52,78]. However, textural indices from Sentinel-1 was marginal in this study for volume mapping compared to the previous finding [79]. It was resulted from the decrease in the heterogeneity by texture analysis and large variations of stand volume in the study area.…”
Section: Multi-sensor Satellite Predictors Of Forest Volume Mappingsupporting
confidence: 87%
“…Haralick suggested a GLCM using 14 second order textural features of remotely sensed images [54]. As there exists no evidence in literature which features are best suitable for biomass prediction in grassland or legume-grass mixtures, eight of these GLCM texture features were used (Table 1), which were provided by the processing tool HaralickTextureExtraction of the Orfeo Toolbox library (OTB, open source, [55]) in QGIS. The eight Haralick texture parameters were computed for all four spectral bands separately with settings on default (window size: 2 × 2) and a texture set selection on "simple".…”
Section: Data Analysis and Machine Learningmentioning
confidence: 99%
“…A total of 1803 30 m by 30 m plots were located and sampled (Figure 1). At each sample site, tree species, diameter at breast height (DBH, the diameter at 1.3 m from the ground), tree height, soil In this study, 18 predictor variables related to forest parameters were selected and extracted from multi-sensors imagery (Tables 3 and 4) [12,[78][79][80]. ALOS-2 PALSAR-2 yearly mosaic image of 2017 was masked and converted to gamma naught values in decibel unit (dB) from 16-bit digital number (DN) ( Table 4) using the following equation [81]: γ 0 = 10 log 10 DN 2 − 83…”
Section: Field Datamentioning
confidence: 99%
“…Previous studies explored numerous Sentinel-2 spectral indices. They found that four vegetation indices and two soil indicators were useful in modelling forest age and soil fertility, respectively [78,80,[83][84][85]. The MSI data had 13 spectral bands with 10 m (bands 2-4, 8), 20 m (band 5-7, 8a, [11][12], and 60 m (band 1, 9-10) spatial resolutions.…”
Section: Field Datamentioning
confidence: 99%